Prognostic impact of anemia and hemoglobin levels in unselected patients undergoing coronary angiography - Steinke, Philipp; Schupp, Tobias; Kuhn, Lasse; Abumayyaleh, Mohammad S. A.; Weidner, Kathrin; Bertsch, Thomas; Schmitt, Alexander; Jannesari, Mahboubeh; Siegel, Fabian; Dürschmied, Daniel; Behnes, Michael; Akın, Ibrahim (Journal of Clinical Medicine, 2024)
Background/Objectives: This study investigates the prevalence and prognostic impact of concomitant anemia in unselected patients undergoing invasive coronary angiography (CA). The spectrum of patients undergoing CA has significantly changed during the past decades, related to ongoing demographic changes and improved treatment strategies for patients with cardiovascular disease. Methods: Consecutive patients undergoing invasive CA from 2016 to 2022 were retrospectively included at one institution. Patients with anemia (i.e., hemoglobin < 13.0 g/dL for males and <12.0 g/dL for females) were compared with patients without anemia (i.e., nonanemics). The primary endpoint was rehospitalization for heart failure (HF) at 36 months. Secondary endpoints comprised the risk of rehospitalization for acute myocardial infarction (AMI) and coronary revascularization. Statistical analyses included Kaplan-Meier, multivariable Cox proportional regression analyses, and propensity score matching. Results: From 2016 to 2022, 7645 patients undergoing CA were included with a median hemoglobin level of 13.2 g/dL. Anemics had a higher prevalence of coronary artery disease (CAD) (76.3% vs. 74.8%; p = 0.001), alongside an increased need for percutaneous coronary intervention (PCI) (45.3% vs. 41.5%; p = 0.001). At 36 months, the risk of rehospitalization for HF was higher in anemic patients (27.4% vs. 18.4%; p = 0.001; HR = 1.583; 95% CI 1.432-1.750; p = 0.001), which was still evident after multivariable adjustment (HR = 1.164; 95% CI 1.039-1.304; p = 0.009) and propensity score matching (HR = 1.137; 95% CI 1.006-1.286; p = 0.040). However, neither the risk of AMI (8.4% vs. 7.4%, p = 0.091) nor the risk of coronary revascularization at 36 months (8.0% vs. 8.5%, p = 0.447) was higher in anemic compared with nonanemic patients. Conclusions: In consecutive patients undergoing CA, concomitant anemia was independently associated with an increased risk of rehospitalization for HF, but not AMI or coronary revascularization. Patients with LVEF ≥ 35% and multivessel disease were especially susceptible to anemia-induced HF-related rehospitalization.